THE EFFECT OF THE MOTIVATIONAL TECHNIQUES ON THE PERFORMANCE OF BIDAR DISTRICTS KABADDI PLAYERS - Mahashetty, Omkar J; Bari, Mohd Abdul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Research suggests that yoga may help improve general wellness. In studies, yoga has helped some people manage stress, improve mental health, lose weight, or quit smoking. There’s also evidence that yoga may be helpful for some medical conditions. Yoga may help lessen pain and menopause symptoms. Yoga improves strength, balance and flexibility. Slow movements and deep breathing increase blood flow and warm up muscles, while holding a pose can build strength. Balance on one foot, while holding the other foot to your calf or above the knee (but never on the knee) at a right angle. A strong core leads to better posture, which can help prevent back and neck problems. Ease stress and anxiety levels. Yoga involves breathing exercises that force you to pay attention to your breath. Deep breathing can help you relax almost instantly, which can help relieve stress and anxiety. The purpose of the present study was to find out the effect of different specific yogic training on selected physical fitness variables among college level male kabaddi Players. To achieve this purpose of the study, fifteen male Kabaddi players who participated in college level kabaddi tournaments were randomly selected as subjects from Bidar District. The age of the subjects were ranged between 18 to 25 years. The selected physical fitness components namely abdominal muscular endurance and flexibility. The data were collected among the male Kabaddi players were statistically analyzed by using student t-test. In all the cases 0 .05 level of confidence was fixed to test the significance. The “t” ratio was employed as a statistical tool to find out the appropriate result of the study and provided significance at 0.05 level of confidence. There was a significant difference between pre and post-test of abdominal muscular endurance, leg explosive power among male Kabaddi players.